1980
DOI: 10.1007/bf03007779
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative sore throat: influence of tracheal tube lubrication versus cuff design

Abstract: The incidence and severity of postoperative sore throat was evaluated in six groups of 20 patients each after elective orthopedic surgery. Groups I to V had tracheal intubalion with Portex disposable polyvinylchloride tracheal tubes and group VI had mask anaesthesia. All groups were exposed to heated humidified gases. Tracheal tubes in groups l-Ill were uncuffed and lubricated with four per cent lidocaine jelly (group I), four per cent lidocaine hydrochloride anaesthetic solution(group I1)or normal saline (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
1
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 7 publications
2
20
1
1
Order By: Relevance
“…Clearly, there are conflicting reports about the effects of using lidocaine jelly as an ETT lubricant and other methods of lidocaine application. In our study, lidocaine spray alone showed a tendency to decrease POST, and lidocaine jelly increased the incidence of sore throat, consistent with the results of Loeser et al [6] and Klemola et al [12]. Fujita et al [13] reported that methylparaben specifically activated the transient receptor potential (TRP) AT channels and can cause pain sensations, especially when applied to the mouth or skin.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Clearly, there are conflicting reports about the effects of using lidocaine jelly as an ETT lubricant and other methods of lidocaine application. In our study, lidocaine spray alone showed a tendency to decrease POST, and lidocaine jelly increased the incidence of sore throat, consistent with the results of Loeser et al [6] and Klemola et al [12]. Fujita et al [13] reported that methylparaben specifically activated the transient receptor potential (TRP) AT channels and can cause pain sensations, especially when applied to the mouth or skin.…”
supporting
confidence: 91%
“…After tracheal intubation, the incidence of POST varies from 14.4% to 50% [4].The main causes of POST are thought to involve traumatic laryngoscopy or contact with the tracheal tube cuff, which may result in edema or erosion of the pharyngeal or tracheal mucosa [5][6][7][8]. Previous studies of the effects of ETT lubricants and lidocaine spray on the incidence of POST have generated inconsistent results [6][7][8][9][10][11][12]. Loeser et al [6] and Jones et al [7] reported that both lignocaine jelly and ointment increased the incidence of sore throat compared with water-soluble jelly or no lubrication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the Chisquare test is applied to the incidence of PST expressed as per cent of the total material, which seems to be the method used by Loeser,et al ,9 there is a significant difference (p < 0.05), with high volume cuffs causing less PST in our study. It should be emphasized that using incidence figures expressed inper cent has the effect that, if the actual material is less than 100, it is increased to 100 in the calculation, i.e.…”
Section: Discussionmentioning
confidence: 51%
“…This was not the case in our investigation. There are probably several explanations of the contradictory results compared with those of Loeser, et al 9 The interview technique may be too blunt an instrument to evaluate and differentiate the pathogenetic factors in PST. This is indicated by the wide variations in results by other authors.…”
Section: Discussionmentioning
confidence: 94%